The Effect Of Quizizz as an Interactive Media on Students' Learning Outcomes in Thermochemistry Material - Zulaeka dJAFAR; Aceng Haetami; Maysara Maysara (PT. Anagata Sembagi Education, 2025)
Research has been conducted on the effect of quizizz as an interactive media on the learning outcomes of students of SMAN 6 Kendari on thermochemical materials. This study aims to determine how much influence quizizz has on student learning outcomes in class XI SMAN 6 Kendari. The research method used was Quasy Experiment with non-equivalent control group design technique. Data collection techniques through tests and observations. The test used is only posttest which is presented as data on student learning outcomes. The samples used were Applied XI class 1 as a control class using conventional learning media and Applied XI class 4 as an experimental class using quizizz learning media. Data processing techniques were carried out with descriptive statistical tests and inferential statistical tests with the T test hypothesis test (Independent sample T-test) assisted by IBM SPSS Statistics 25 software. Based on the results of the study, it shows that there is a significant effect on quizizz learning media on student learning outcomes. This is proven by using the T test with a sig value. (2-tailed) 0.026 <0.05. From the results of this study it can be concluded that quizizz learning media has an effect on student learning outcomes.